2002
DOI: 10.1007/s00426-002-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor capture and Inhibition of Return: Evidence for an oculomotor suppression account of IOR

Abstract: Previous research has shown that when sub-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
56
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 59 publications
7
56
1
Order By: Relevance
“…Because of the presumed stimulus-driven nature of these saccades to the onset, they have been referred to as oculomotor capture. Subsequent research has replicated the major findings of Theeuwes et al, although the degree to which onsets capture the eyes varies widely between different versions of the oculomotor capture task (e.g., Godijn & Theeuwes, 2002b;Irwin, Colcombe, Kramer, & Hahn, 2000) and some studies have found a much lower frequency of oculomotor capture by onsets under certain conditions (e.g., Godijn & Kramer, 2006;Ludwig & Gilchrist, 2002). Although a comparison of these studies is complicated due to the many differences in the stimulus displays, one factor that likely contributes to the percentage of oculomotor capture is the saccade latency distribution.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…Because of the presumed stimulus-driven nature of these saccades to the onset, they have been referred to as oculomotor capture. Subsequent research has replicated the major findings of Theeuwes et al, although the degree to which onsets capture the eyes varies widely between different versions of the oculomotor capture task (e.g., Godijn & Theeuwes, 2002b;Irwin, Colcombe, Kramer, & Hahn, 2000) and some studies have found a much lower frequency of oculomotor capture by onsets under certain conditions (e.g., Godijn & Kramer, 2006;Ludwig & Gilchrist, 2002). Although a comparison of these studies is complicated due to the many differences in the stimulus displays, one factor that likely contributes to the percentage of oculomotor capture is the saccade latency distribution.…”
mentioning
confidence: 68%
“…Although a comparison of these studies is complicated due to the many differences in the stimulus displays, one factor that likely contributes to the percentage of oculomotor capture is the saccade latency distribution. Specifically, previous studies have found that saccades to the onset have shorter latencies than saccades to the target (e.g., Godijn & Theeuwes, 2002b;Theeuwes et al, 1998). Indeed, in Godijn and Kramer (2006) oculomotor capture was negligible and saccade latencies to the colour singleton target were around 300 ms, while in earlier studies (Godijn & Theeuwes, 2002b;Theeuwes et al, 1998Theeuwes et al, , 1999 there was about 30% oculomotor capture and mean saccade latencies to the target were around 220 ms.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, Miller (1989) showed that attention is not only controlled by sudden onsets, but that attention is attracted by all sudden changes in a visual scene. Indeed, in line with the dynamic default hypothesis (Franconeri and Simons 2003), which states that all dynamic events garner attentional priority, different types of motion, such as the start of movement (e.g., Abrams and Christ 2003), moving, looming, and disoccluding objects (Franconeri and Simons 2003) may draw attention and cause people to fixate on the target object (Godijn and Theeuwes 2002). However, it is important to note that motion per se does not attract attention.…”
Section: Theoretical Accounts Of the Effect Of Cueing On Perceptual Amentioning
confidence: 92%